On the Determination of Uncertainty and Limit of Detection in Label-Free Biosensors - Lavín, Álvaro; Vicente, Jesús de; Holgado, Miguel; Laguna, María F.; Casquel, Rafael; Santamaría, Beatriz; Maigler, María Victoria; Hernández, Ana L.; Ramírez, Yolanda (Sensors (Basel, Switzerland), 2018)
A significant amount of noteworthy articles reviewing different label-free biosensors are being published in the last years. Most of the times, the comparison among the different biosensors is limited by the procedure used of calculating the limit of detection and the measurement uncertainty. This article clarifies and establishes a simple procedure to determine the calibration function and the uncertainty of the concentration measured at any point of the measuring interval of a generic label-free biosensor. The value of the limit of detection arises naturally from this model as the limit at which uncertainty tends when the concentration tends to zero. The need to provide additional information, such as the measurement interval and its linearity, among others, on the analytical systems and biosensor in addition to the detection limit is pointed out. Finally, the model is applied to curves that are typically obtained in immunoassays and a discussion is made on the application validity of the model and its limitations.